2011
DOI: 10.1017/s0007114511002339
|View full text |Cite
|
Sign up to set email alerts
|

Different variations of tissue B-group vitamin concentrations in short- and long-term starved rats

Abstract: Prolonged starvation changes energy metabolism; therefore, the metabolic response to starvation is divided into three phases according to changes in glucose, lipid and protein utilisation. B-group vitamins are involved in energy metabolism via metabolism of carbohydrates, fatty acids and amino acids. To determine how changes in energy metabolism alter B-group vitamin concentrations during starvation, we measured the concentration of eight kinds of B-group vitamins daily in rat blood, urine and in nine tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Shibata et al 7) reported that mild food restriction reduced tryptophan-nicotinamide conversion, which helps to explain why death secondary to pellagra is pandemic during the "hungry season" which is defined as off-season of food production. In contrast, Shibata et al 1,2,6) reported that severe food restriction increased tryptophan-nicotinamide conversion because the availability of free-type tryptophan increases with body protein breakdown. Therefore, we proposed that a greater amount of preformed niacin should be ingested during mild food restriction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Shibata et al 7) reported that mild food restriction reduced tryptophan-nicotinamide conversion, which helps to explain why death secondary to pellagra is pandemic during the "hungry season" which is defined as off-season of food production. In contrast, Shibata et al 1,2,6) reported that severe food restriction increased tryptophan-nicotinamide conversion because the availability of free-type tryptophan increases with body protein breakdown. Therefore, we proposed that a greater amount of preformed niacin should be ingested during mild food restriction.…”
Section: Discussionmentioning
confidence: 94%
“…1) We also investigated the effects of long-term (eight-day) starvation on the urinary excretion of B-group vitamins in rats and found that the amounts of all B-group vitamins in urine were decreased by longterm starvation but that the B-group vitamin concentrations in the liver remained almost unchanged. 2) Food restriction, namely energy restriction, is generally characterized by delayed growth and leads to changes in nutrient metabolism. Some reports have revealed the use of preferred phenomena for health maintenance by calorie restriction, such as longevity [3][4][5] and prevention of oocyte aging.…”
mentioning
confidence: 99%
“…Tissue levels of pantothenate in mammals are very low (rats, 109 Ϯ 7 nmol/g; human colon, 5.9 Ϯ 0.4 nmol/g) (48,49). Inhibitors of E. coli and M. tuberculosis pantothenate synthetase have been designed, and M. tuberculosis auxotrophic mutants with mutations in pantothenate biosynthetic enzymes are attenuated in animals (50).…”
Section: Discussionmentioning
confidence: 99%
“…Our group reported that urinary excretion levels of water-soluble vitamins reflect recent 1-week intakes of these vitamins 14. In addition, we reported that fasting and starvation alters urinary excretion levels of water-soluble vitamins in humans and rats 5,6. The most striking phenomena were the sharp decrease in urinary excretion of vitamin B 1 in humans and rats,5,6 increased urinary excretion of vitamin B 2 in humans,5 and decreased urinary excretion of vitamin B 2 in rats 5,6.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, we reported that fasting and starvation alters urinary excretion levels of water-soluble vitamins in humans and rats 5,6. The most striking phenomena were the sharp decrease in urinary excretion of vitamin B 1 in humans and rats,5,6 increased urinary excretion of vitamin B 2 in humans,5 and decreased urinary excretion of vitamin B 2 in rats 5,6. These findings showed that urinary excretion levels of water-soluble vitamins do not always reflect intake or nutritional status during fasting and starvation, particularly in terms of vitamins B 1 and B 2 .…”
Section: Introductionmentioning
confidence: 99%